Does money buy credit? Firm-level evidence on bribery and bank debt - Zuzana Fungáčová; Laurent Weill; Anna Kochanova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
This study examines how bribery influences bank debt ratios for a large sample of firms from 14 transition countries. We combine information on bribery practices from the BEEPS survey with firm-level accounting data from the Amadeus database. Bribery is measured by the frequency of extra unofficial payments to officials to "get things done". We find that bribery is positively related to firms' bank debt ratios, which provides evidence that bribing bank officials facilitates firms' access to bank loans. This impact differs with the maturity of bank debt, as bribery contributes to higher short-term bank debt ratios but lower long-term bank debt ratios. Finally, we find that the institutional characteristics of the banking industry influence the relation between bribery and firms' bank debt ratios. Higher levels of financial development constrain the positive effects of bribery whereas larger market shares of state-owned banks have the opposite effect. Foreign bank presence also affects the impact of bribery, albeit this effect depends on the maturity of firms' bank-debt.
URN:NBN:fi:bof-201408071990
Keywords: G32; K4; P2; 330; bank lending; bribery; corruption; Eastern Europe